ANALISIS VARIABEL MAKROEKONOMI TERHADAP KINERJA REKSADANA CAMPURAN - Augustina Kurniasih; Leonardo David Yuliandy Johannes (Jurnal Manajemen., 2015)
Nowadays investment instruments are growing. One of the investment instruments is mutual fund. Indonesian macroeconomic conditions affected the performance of investments, including on mutual funds. One type of mutual fund is balance mutual funds. This study aims to examine and analyze the effect of stock index returns, return of USD exchange rate, return of JIBOR Interest Rate, and return of government bonds of Indonesia to the performance of balance mutual funds. Observation period is one year (2012), using daily data. Total balance mutual funds in IDX are 120, which meets the criteria of the sample were 86. Method used to answer the research problem is multiple linear regressions. It found that macroeconomic factors that significantly influence the performance of balance mutual funds are returns JCI and JIBOR interest rate return.